BRAIN DISEASES AND SPEECH LOSS - Bobokalonov Ramazon Radjabovich; Ganiyeva Zebo Shavkat kizi (Bright Mind Publishing, 2025)
The article summarizes information about brain diseases and problems of speech loss. Its purpose is to study the causes of speech delay, impairment and loss due to various types of diseases and to explain its main causes. The article is intended for students studying at the bachelor's and master's levels.
Keywords: Brain diseases, strokes, brain tumors, aphasia, language, dysarthria, motor speech, communication methods, injuries, tumors, neurological diseases: Alzheimer's disease and multiple sclerosis.